MiR-502 Suppresses TNF-α-Induced Nucleus Pulposus Cell Apoptosis by Targeting TARF2. (2nd April 2021) - Guo, Zhao; Gao, Wen-Shan; Wang, Yun-Fei; Gao, Fei; Wang, Wei; Ding, Wen-Yuan
Abstract : Intervertebral disc degeneration (IVDD) is a common cause of low back pain. This study is aimed at investigating the role of microRNAs (miRNAs) in regulating human nucleus pulposus (NP) cell injury induced by tumor necrosis factor- (TNF-) α in IVDD. In this study, we induced NP cells with 20 ng/mL TNF- α in vitro, which promoted the obvious apoptosis of NP cells and the activation of nuclear transcription factor (NF)- κ B. In contrast, using the specific NF- κ B inhibitor BAY 11-7082 to treat cells greatly impaired the activation of NF- κ B and increased the sensitivity of NP cells to TNF- α -induced apoptosis. Moreover, both TNF- α and BAY 11-7082 treatments were associated with marked miRNA dysregulation, with miR-502 being upregulated by TNF- α treatment and downregulated by BAY 11-7082 treatment, respectively. And the overexpression of miR-502 enhanced NF- κ B activation and suppressed apoptosis of human NP cells induced by TNF- α, whereas the opposite was observed following miR-502 inhibition. Last, through bioinformatic analyses and luciferase reporter gene experiments, we identified TRAF2, an important activator of NF- κ B, as a miR-502 target gene. Similarly, siRNA-mediated knockdown of the TRAF2 expression also suppressed TNF- α -induced apoptosis and enhanced NF- κ B activation. Our findings provide evidence indicating that miR-502 is a key regulator of apoptosis of human NP cells induced by TNF- α by targeting TRAF2 and activating NF- κ B.